IMPLEMENTASI GERAKAN LITERASI DI SEKOLAH (STUDI KASUS DI SDN KARAH 1 SURABAYA) - Retno Nuzilatus Shoimah (Universitas Islam Darul 'Ulum Lamongan, 2020)
AbstractSchool is one of the educational facilities chosen by the government as theimplementation center of the program